Stable inheritance of telomere chromatin structure and function in the absence of telomeric repeats - Sadaie, Mahito (Cold Spring Harbor Laboratory Press, 2003)
It is generally believed that telomeric repeats are a necessary and sufficient cis-element for telomere function. Here we show that telomere structure and meiotic function are stably inherited in fission yeast circular chromosomes that have lost all telomeric repeats. We found that the telomeric repeat binding protein, Taz1, and the heterochromatin protein, Swi6, remain associated with subtelomeres in the absence of telomeric repeats. We also found that the fusion point of circular chromosomes that lack telomeric repeats associates with SPB (the yeast counterpart of the centrosome) in the premeiotic horsetail stage, similarly to wild-type telomeres. However, a taz1(+) deletion/reintroduction experiment revealed that the maintenance of Taz1 binding and premeiotic function is achieved via different strategies. Taz1 is recruited to subtelomeres by an autonomous element present in subtelomeric DNA, thus in a genetic mechanism. In contrast, the premeiotic subtelomere-SPB association is maintained in an epigenetic manner. These results shed light on the previously unrecognized role played by the subtelomere and underscore the robust nature of the functional telomere complex that is maintained by both genetic and epigenetic mechanisms. Furthermore, we suggest that the establishment and the maintenance of the functional telomere complex are mechanistically distinguishable.